Efekti barijatrijske i metaboličke operacije na aktivnost sinteze žultske kiseline, gena konjugacije enzima i funkciju bukozalne barijere (D-LA, Zonulin-E8) u dijabetičkim bolesnicima: Alterations in Bile Acids before and following Bariatric and Metabolic Surgery for Diabetes - Zhang, Jingjing; Apaer, Shadike; Zhang, Shuo; Liang, Guanyou; Li, Tao; Cao, Xinling (Journal of Medical Biochemistry, 2025)
Objective: To observe the changes of bile acid synthase activity, conjugation enzyme gene and intestinal mucosal barrier function (D-LA, Zonulin, MFG-E8) in patients with type 2 diabetes mellitus (T2DM) after bariatric and metabolic surgery (BMS), and to provide an objective opinion on the clinical optimization of BMS. Methods: 127 patients with T2DM who had received BMS treatment at our hospital from October 2023 to August 2024 were included in the study, and weight loss, glucose-lipid metabolism was detected before surgery and at 6 months after surgery. Furthermore, the study quantified the expression levels of key enzymes involved in bile acid synthesis and conjugation (CYP7A1, CYP27A1, FXR, FGF19) and markers indicative of intestinal mucosal barrier function (D-LA, Zonulin, MFG-E8). Results: After BMS, the patient’s weight was significantly reduced and glucolipid metabolism was significantly improved (P<0.05). In addition, CYP7A1 was decreased and FXR, FGF19 was elevated in patients after surgery (P<0.05). Regarding the intestinal mucosal barrier function, D-LA, Zonulin were decreased in patients after surgery (P<0.05). MFG-E8 was not significantly altered after surgery in patients with sleeve gastrectomy (P>0.05), while it was elevated after surgery in patients with Roux-en-Y gastric bypass compared to baseline (P<0.05). Conclusion: BMS can effectively improve glucose-lipid metabolism and reduce body weight in T2DM patients, and its mechanism is related to regulating bile acid metabolism and promoting the recovery of intestinal barrier function.